Syndemic effects of HIV risk behaviours: results from the NHANES study. (2019) - Smith, L.; Cao, C.; Zong, X.; McDermott, D. T.; Stefanac, S.; Haider, S.; Jackson, S. E.; Veronese, N.; López-Sánchez, G. F.; Koyanagi, A.; Yang, L.; Grabovac, I.
Abstract: The aim of the present study is to use the syndemic framework to investigate the risk of contracting HIV in the US population. Cross-sectional analyses are from The National Health and Nutrition Examination Survey. We extracted and aggregated data on HIV antibody test, socio-demographic characteristics, alcohol use, drug use, depression, sexual behaviours and sexually transmitted diseases from cycle 2009–2010 to 2015–2016. We carried out weighted regression among young adults (20–39 years) and adults (40–59 years) separately. In total, 5230 men and 5794 women aged 20–59 years were included in the present analyses. In total, 0.8% men and 0.2% women were tested HIV-positive. Each increasing HIV risk behaviour was associated with elevated odds of being tested HIV-positive (1.15, 95% CI 1.15–1.15) among young adults and adults (1.61, 95% CI 1.61–1.61). Multi-faceted, community-based interventions are urgently required to reduce the incidence of HIV in the USA.